The application of precautionary principle in International Trade Law and International Environmental Law: A comparison - Ansari, Abdul Haseeb; -, Sri Wartini (2013)
Precautionary principle, which developed as a soft law, became part of the Cartagena Protocol and the SPS Agreement aims at ensuring biosafety of GMOs, which includes LMOs to human health in particular and conservation of the environment in general. But the provisions of the two hard laws are not the same as they serve two different purposes. Although conservation of the environment is sine qua non for survival of the humankind, the WTO had preferred to apply the provisions enshrined in the SPS Agreement, which prescribes for weaker precautionary measure, as its aim is to promote international trade. What is warranted is that both the laws have to be interpreted in order to strike a balance between the two so that trade and environment thrive together. It is for this reason that the paper presents a comparative assessment of both the laws, and attempts present a comprehensive precautionary principle so that both the laws could get due importance.